Awareness and Need for Dental Insurance in India: A Survey-Based Study Among Dental Health Care Professionals - Nileshwariba Jadeja; Ruchik Anerao; C. Nandini; Chaitanya Buddhikot; Anuraga Sekharamantri; Pooja Singh; Freya Mehul Gandhi (Journal of Pharmacy and Bioallied Sciences)
Background: Oral health is vital to overall well-being, but high dental care costs often restrict access, particularly in developing countries like India. Although dental insurance could alleviate these costs and enhance accessibility, it remains underdeveloped in Southeast Asia, including India. Objective: This study evaluates the awareness and perceived need for dental insurance among dental health professionals and students in India, focusing on their views regarding its role in improving care accessibility. Methods: An online cross-sectional survey was administered to 500 participants (dentists and dental students) at a dental college in Gandhinagar, India. Data from 474 completed responses were analyzed after excluding 26 incomplete ones. The survey covered personal demographics, insurance status, perceptions of dental care costs, and interest in dental insurance. Results: The survey revealed a significant demand for dental insurance. A substantial 85.3% of participants found private dental treatments costly, and 90.6% viewed dental insurance was as crucial as medical insurance. Furthermore, 76.7% showed interest in learning more about dental insurance. Conclusion: Integrating dental insurance into India's healthcare system could enhance dental care access by lowering financial barriers. Increased awareness and education about dental insurance among dental professionals and students are essential to address existing gaps and improve oral health outcomes.